Effect of prenatal DHA supplementation on the infant epigenome: results from a randomized controlled trial. Issue 1 (December 2016) - van Dijk, Susan; Zhou, Jing; Peters, Timothy; Buckley, Michael; Sutcliffe, Brodie; Oytam, Yalchin; Gibson, Robert; McPhee, Andrew; Yelland, Lisa; Makrides, Maria; Molloy, Peter; Muhlhausler, Beverly
Abstract Background Evidence is accumulating that nutritional exposures in utero can influence health outcomes in later life. Animal studies and human epidemiological studies have implicated epigenetic modifications as playing a key role in this process, but there are limited data from large well-controlled human intervention trials. This study utilized a large double-blind randomized placebo-controlled trial to test whether a defined nutritional exposure in utero, in this case docosahexaenoic acid (DHA), could alter the infant epigenome. Pregnant mothers consumed DHA-rich fish oil (800 mg DHA/day) or placebo supplements from 20 weeks' gestation to delivery. Blood spots were collected from the children at birth (n = 991) and blood leukocytes at 5 years (n = 667). Global DNA methylation was measured in all samples, and Illumina HumanMethylation450K BeadChip arrays were used for genome-wide methylation profiling in a subset of 369 children at birth and 65 children at 5 years. Results There were no differences in global DNA methylation levels between the DHA and control group either at birth or at 5 years, but we identified 21 differentially methylated regions (DMRs) at birth, showing small DNA methylation differences (<5%) between the treatment groups, some of which seemed to persist until 5 years. The number of DMRs at birth was greater in males (127 DMRs) and in females (72 DMRs) separately, indicating a gender-specific effect. Conclusion Maternal DHA supplementation during the second half of pregnancy had small effects on DNA methylation of infants. While the potential functional significance of these changes remains to be determined, these findings further support the role of epigenetic modifications in developmental programming in humans and point the way for future studies. Trial registration Australian New Zealand Clinical Trials Registry (ANZCTR), ACTRN12605000569606 andACTRN12611001127998